Hybrid forms: translating Boethius in Anglo-Saxon England. (24th July 2017) - Weaver, Erica
Abstract: Critics have long wondered about the setting and intent of the Old English translation of Boethius's De consolatione philosophiae, first into prose and then into prosimetrum. This article situates the dual translation within the broader context of ninth- and tenth-century literary culture, challenging the received view of the two versions as separate projects and arguing instead that the Old English Boethius was conceived and received as a vernacular opus geminatum, or 'twinned work'. While the opus geminatum and the prosimetrum are generally thought to maintain distinct generic identities, this case study allows for a more capacious understanding of both modes, which I demonstrate were inescapably linked in Anglo-Saxon circles – and which were shaped by a broader aesthetic of prose-verse mixture.